Influence of Soil pH on Azotobacter Population With Using Microbiological Characteristics as Bio-Measurement in Arable Lands of Tripoli. N. W. Libya - Ben Mahmud, Merfat T.; Ferjani, Eman A. (Al-Mukhtar Journal of Sciences, 2018)
In the present study, 15 samples of soil were collected to isolate Azotobacter from the rhizosphere in different regions of Tripoli. LG specified medium was used for the isolation of bacteria and were purified on the same medium for identification and characterisation.The colonies were identified through microscopical and biochemical tests and the results obtained were classified as Azotobacter sp. Subsequently, the microbial population was calculated by colony count method. The soil pH, total nitrogen content (N), total phosphorus content (P) and organic carbon (OC) in soil were determined. The results of this study indicated to effects positive and negative of soil pH levels on Azotobacter population. In the estimation of above chemical properties of all soil samples it was showed that bacterial population differs significantly among the different soil samples.